Preliminary Experimental Study on Double Fuel HCCI Combustion. (December 2015) - Genchi, Giuseppe; Pipitone, Emiliano
Abstract: This paper regards an experimental study on a particular internal combustion engine process which combines Double Fuel combustion with Homogeneous Charge Compression Ignition (HCCI) using mixtures of natural gas (NG) and gasoline. The tests performed on a CFR engine demonstrate that HCCI combustion can be achieved using NG-gasoline mixtures without knocking occurrence for low to medium engine load varying the proportion between the two fuels. The main advantage of this new combustion process relies on the noticeable higher engine efficiency obtained with respect to conventional spark ignition operation, and on the strong reduction of NOX emissions.